Challenges of Good Governance in Nigeria (2011-2019) - Oji, Okechukwu Richard (Direct Research Journal of Social Science and Educational Studies, 2024)
This paper critically explores the challenges of good governance in Nigeria. Good governance is the quest of nations all over the world; it implies accountability, transparency, prevalence of the rule of law and popular participation. There is strong evidence that good governance matters in accelerating development and in reducing poverty in most countries of the world. Advocates have linked the advancement of a variety of issues to improved governance. Nigeria is a developing nation that has encountered significant governance challenges since its inception in 1960. These challenges have been manifested in the form of corruption, political instability, weak institutions, and lack of accountability, which have had a negative impact on the country's progress and have contributed to a range of social, economic, and political issues. The main objective of this study therefore, is to assess the practice and challenges of good governance in Nigeria. The paper employs a qualitative methodology that heavily relies on secondary sources of data from books, journals, and web-based materials, among others. The study found that good governance practices in Nigeria were hindered by various factors, such as, corruption, legitimacy crisis, disregard for constitutional provisions, and weak institutions which have led to mass poverty, deplorable living conditions, crimes and general insecurity as people struggle to survive under the harsh conditions of poverty. The study therefore recommends for strengthening of weak institutions, strong reinforcing of accountability and transparency in governmental institutions, enhance effective fight against corruption and those caught must be prosecuted and brought to justice regardless of position, class or tribe. The study suggests also, that the government should respect the rule of law and obey the constitutional provisions in order to entrench and safeguard stability in governance in Nigeria. Finally it suggests for use of modern security strategies in dealing with the menace of insecurity.
Keywords: Good governance; principles of good governance; challenges; Nigeria